The Electronic Freedom of Information Improvement Act : hearing before the Subcommittee on Technology and the Law of the Committee on the Judiciary, United States Senate, One Hundred Second Congress, second session, on S. 1940, a bill to amend Title 5, United States Code, to provide for public access ... April 30, 1992. (1993)
Summary goes here